The Influence of Experiential Marketing and Customer Satisfaction toward Customer Loyalty on Cipanas Hot Spring Garut - Edwin Rizki Sukmaputra (Prosiding Industrial Research Workshop and National Seminar, 2018)
Indonesia as a country with a huge tourism potential, there should be special attention to be utilized maximally. The simplest step is developing the nature tourism, for example hot spring tourism. West Java can become a potential for burgeoning of hot spring tourism such as Garut. It has a popular hot spring tourism called Cipanas. The evaluation can be gotten through knowing customer experience who have visited Cipanas. Experiential Marketing theory becomes a complete solution in knowing the customer experience in detail. This experience will be related to how the satisfaction and loyalty of tourists after visited Cipanas hot spring. In addition, it shows which gap that needs a special attention. The research objective is to determine how the influence of experiential marketing and customer satisfaction toward customer loyalty as a best practice on advancement of Cipanas hot spring tourism. The data that will be obtained is by spreading questionnaires that contains in-depth questions about the three variables. The target of the respondents is 200 with qualification; domestic tourists and residents. The output will be seen by virtue of the gap on experiential marketing dimensions to evaluate effectively. Researcher believes that this research will help gradually the Indonesian economy.